Archaeological sites of residence – bronze age settlements in the Volga-Manych steppes - M. A. Ochir-Goryaeva (Nomadic Civilization: Historical Research)
The relevance of the study of archaeological sites of residence – a Bronze Age settlement in the Volga-Manych steppes – lies in the fact that in Russian science the place of residence has not been studied and studies on them have been published in small quantities, in contrast to funerary monuments-barrows. The main reason for this “inattention” on the part of scientists lies in the small size of these settlements, which is why they are usually referred to as “seasonal camps of mobile cattle breeders” rather than permanent dwellings. Nevertheless, a targeted search for settlements of the Bronze and Early Iron Age on the territory of our country was conducted and is being carried out by many archaeologists, including the author of this study. During excavations in the Volga-Manych steppes, hundreds of places of residence or sites were discovered. One of them is a settlement found in 1976 by E.V. Schneidstein on the territory of the Republic of Kalmykia, on the shore of Lake Zakhanata. Additional studies of the archaeological site, conducted by us in 2002, showed that there are two settlements of the carcass culture. In this article, we continued a detailed study of this unique cultural monument located in the Kalmyk steppe. The materials of the study allowed us to identify the general and special features of settlements in the Bronze Age in the Volga region as part of the steppes from the Carpathians to the Urals, to determine the type of farms of the tribes inhabiting this area, contributed to the formation of a more or less clear idea of the cultural and historical processes taking place on the territory in the historical period.